A circuit for detection of interaural time differences in the brain stem of the barn owl - Carr, CE (J Neurosci, 1990)
Detection of interaural time differences underlies azimuthal sound localization in the barn owl Tyto alba. Axons of the cochlear nucleus magnocellularis, and their targets in the binaural nucleus laminaris, form the circuit responsible for encoding these interaural time differences. The nucleus laminaris receives bilateral inputs from the cochlear nucleus magnocellularis such that axons from the ipsilateral cochlear nucleus enter the nucleus laminaris dorsally, while contralateral axons enter from the ventral side. This interdigitating projection to the nucleus laminaris is tonotopic, and the afferents are both sharply tuned and matched in frequency to the neighboring afferents. Recordings of phase-locked spikes in the afferents show an orderly change in the arrival time of the spikes as a function of distance from the point of their entry into the nucleus laminaris. The same range of conduction time (160 mu sec) was found over the 700-mu m depth of the nucleus laminaris for all frequencies examined (4-7.5 kHz) and corresponds to the range of interaural time differences available to the barn owl. The estimated conduction velocity in the axons is low (3-5 m/sec) and may be regulated by short internodal distances (60 mu m) within the nucleus laminaris. Neurons of the nucleus laminaris have large somata and very short dendrites. These cells are frequency selective and phase-lock to both monaural and binaural stimuli. The arrival time of phase-locked spikes in many of these neurons differs between the ipsilateral and contralateral inputs. When this disparity is nullified by imposition of an appropriate interaural time difference, the neurons respond maximally. The number of spikes elicited in response to a favorable interaural time difference is roughly double that elicited by a monaural stimulus. Spike counts for unfavorable interaural time differences fall well below monaural response levels. These findings indicate that the magnocellular afferents work as delay lines, and the laminaris neurons work as co- incidence detectors. The orderly distribution of conduction times, the predictability of favorable interaural time differences from monaural phase responses, and the pattern of the anatomical projection from the nucleus laminaris to the central nucleus of the inferior colliculus suggest that interaural time differences and their phase equivalents are mapped in each frequency band along the dorsoventral axis of the nucleus laminaris.